(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Enteric fever, specially Typhoid fever is endemic in Bangladesh. Due to lack of clean water, sanitation, and proper awareness it is more common in urban area and slum area of cities. Its diagnosis poses several problems, after diagnosis, it is important to treat with the right antibiotic before any complications can occur. Objective: Aim of the study was to assess the current susceptibility pattern of typhoidal salmonellae to antimicrobial using for treatment of typhoid fever. Methods: A prospective observational study was carried out for blood culture positive Typhoid fever admitted in Dhaka Shishu Hospital, during the period of May 2017 to April 2018. Children from 1year to 15 years with blood culture positive for S.Typhi and S.Para Typhi were included in this study. Results: One hundred ten strain of Salmonella typhi and paratyphi were isolated from June 2017 to July 2018. Out of 110 isolated, 97 (88%) were Salmonella typhi and 13(12%) were paratyphi. Among them sensitivity to Ceftriaxone was 90 %( 99) and cefixime 80% (88). Sensitivity to other drugs was Ampicillin or Amoxicillin 54%, Chloramphenicol 48%, Ciprofoxacin 42%, Azithromycin 38%, Co-trimoxazole 20% respectively. Conclusion: In this study antimicrobial sensitivity testing showed that SalmonellaeTyphi as well as para typhi were not 100% sensitive to any drug. Besides this, study showed sensitivity reduce to 60% to 20 to previously used first line drugs and fluoroquinolone groups for treatment of typhoid fever. So judicial use of appropriate antibiotics for treatment of typhoid fever needed DS (Child) H J 2018; 34(1) : 11-14